Short Communication: Antibacterial effect of red betel (Piper crocatum) extract in combination with vancomycin against Staphylococcus aureus - Yustina Sri Hartini; Laurentius Hartanto Nugroho (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Hartini YS, Nugroho LH. 2020. Short Communication: Antibacterial effect of red betel (Piper crocatum) extract in combination with vancomycin against  Staphylococcus aureus. Biodiversitas 21: 3271-3274.  The occurrence of bacterial resistance to a single antimicrobial compound has prompted the search for antimicrobials in the form of compound combinations. The current study was performed to show the antibacterial effect of red betel (Piper crocatum Ruiz & Pav.) in combination with vancomycin against Staphylococcus aureus. The combination of the antibacterial compounds from plant with the antibacterial drug was expected to increase antibacterial activity resulted in the reduction of resistance. The interaction effect of extract and antibiotic combination was performed using the microdilution checkerboard method. The combination of red betel extract with vancomycin showed significantly (p < 0.05) greater inhibition growth of S. aureus compared to red betel or vancomycin alone. The addition of red betel extract to vancomycin reduced Minimum Inhibitory Concentration (MIC) vancomycin to be a-4 fold reduction against S. aureus. There was a synergistic effect of the red betel extract in combination with vancomycin against S. aureus. It is the potential result for future research on the infectious treatment of S. aureus resistant to vancomycin.